Purification and characterization of sheep brain cold-stable microtubules. - Pirollet, F (1983)
The isolation of cold-stable microtubules in high yields, described previously only from rodents, was extended to the brain of higher animals. Under optimal conditions, yields of 30 mg of cold-stable microtubles per 100 g of sheep brain could be obtained routinely. Material purified by two polymerization cycles displayed the same stability to cold temperature or to millimolar concentrations of calcium and the same lability to calmodulin and to ATP as did the purified material obtained from the rat [Job, D., Rauch, C.T., Fischer, E.H. & Margolis, R.L. (1982) Biochemistry 21, 509]. Furthermore, DE-52 chromatography of this material yielded a fraction that restored cold stability when added to cold-labile microtubules. Known to bind to calmodulin and to enhance microtubule assembly, tau proteins had no cold-stabilizing activity. Protein profiles of the cold-stabilizing fraction from sheep and rat brain were similar to one another but showed no protein bands corresponding to the tau proteins.